Polyamide 12 Materials Study of Morpho-Structural Changes during Laser Sintering of 3D Printing - Simha Martynková, Gražyna; Slíva, Aleš; Kratošová, Gabriela; Čech Barabaszová, Karla; Študentová, Soňa; Klusák, Jan; Brožová, Silvie; Dokoupil, Tomáš; Holešová, Sylva (Polymers, 2021)
The polyamide (PA)-12 material used for additive manufacturing was studied in aspects of morphology and their structural properties for basic stages received during 3D laser printing. Samples were real, big-scale production powders. The structure of polymer was evaluated from the crystallinity point of view using XRD, FTIR, and DSC methods and from the surface properties using specific surface evaluation and porosity. Scanning electron microscopy was used to observe morphology of the surface and evaluate the particle size and shape via image analysis. Results were confronted with laser diffraction particles size measurement along with an evaluation of the specific surface area. Fresh PA12 powder was found as inhomogeneous in particle size of material with defective particles, relatively high specific surface, high lamellar crystallite size, and low crystallinity. The scrap PA12 crystallinity was about 2% higher than values for fresh PA12 powder. Particles had a very low, below 1 m2/g, specific surface area; particles sintered as twin particles and often in polyhedral shapes.
Keywords: PA12; morphology; 3D print; structure